1994
DOI: 10.1080/11250009409355897
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomes and microevolutionary processes

Abstract: The role of chromosomal rearrangement in microevolutionary processes is discussed, considering numerous aspects of the complex mechanisms of chromosomal speciation. The different degrees of chromosome-derived subfertility, a consequence of the different kinds of structural heterozygosities in the inter-racial hybrids, are discussed with reference to the effectiveness of the postmating reproductive barrier. A «non meiotic» view of the reproductive fitness of the Robertsonian heterozygotes and homozygotes is pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
27
0
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 49 publications
2
27
0
1
Order By: Relevance
“…Another more plausible explanation is the so-called fusion effect of Capanna and Redi (1994), which is consistent with modern research on the interphase nucleus structure. The chromosomes tend to occupy exclusive territories in the interphase nuclei and there is a correlation between nuclear architecture and gene expression.…”
Section: Discussionsupporting
confidence: 81%
“…Another more plausible explanation is the so-called fusion effect of Capanna and Redi (1994), which is consistent with modern research on the interphase nucleus structure. The chromosomes tend to occupy exclusive territories in the interphase nuclei and there is a correlation between nuclear architecture and gene expression.…”
Section: Discussionsupporting
confidence: 81%
“…In the case of balanced rearrangements, structural reorganization of chromosomes may induce changes that could play an important role in modifying and/or disrupting some of the coadapted gene systems. These modifications may involve losses in DNA content such as those observed in telomeric sites and satellite DNA for Rb fusions in house mice (Garagna et al 1995;Nanda et al 1995), or changes in recombination patterns and rates (Dutrillaux 1986;Davisson and Akeson 1993;Eyrewalker 1993;Qumsiyeh 1994;Nevo et al 1995), and in the position of chromosomes within the interphasic nucleus with potential consequences on gene expression (Capanna and Redi 1994;Qumsiyeh 1995). In this study, the two chromosomal races showed no differences in the levels of FA of tooth characters, which suggests that genomic coadaption has not been disrupted by the new chromosomal organization of the genome.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the lower level of DS in Tunisian hybrids suggests that a breakdown of genomic coadaption has occurred and, consequently, that the genome of the Tunisian Rb race has sufficiently diverged from the all-acrocentric one to reach the incompatibility threshold. However, such incompatibilities were not predicted from the low level of allozyme divergence between these two races (Nei's genetic distance, D Nei = 0.07; Said and Britton-Davidian 1991), unless differentiation of genes specifically in- 4-7 9 Number of heterozygous fusions could lead to distorted cytodifferentiation pathways in early stages of germ cell development (Redi and Capanna 1988), thus affecting reproductive fitness in hybrids (Capanna and Redi 1994). Such features related to the multiplication and differentiation of cells may also concern development, suggesting that DS could be impaired in chromosomal hybrids between taxa showing only slight genic differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations